Performance and Emissions Characteristics of Crude Jatropha Oil Biodiesel Blends in a Diesel Engine - Abdul Adam, Abdullah; Amir, Khalid; N., Jaat; A., Sapit; A., Razali; Bukhari, Manshoor; Izzuddin, Zaman (Universiti Malaysia Pahang, 2015)
Biofuels based on vegetable oils offer the advantages of being sustainable, annually renewable sources of automobile fuel. Despite many years of improvement, use of vegetable-oil-based fuels still has issues, such as oxidation, the stoichiometric point, bio-fuel composition, antioxidants on degradation and the volume of oxygen compared to diesel. Thus, improvements in the emissions from diesel engines fueled by a blend of crude jatropha oil with diesel could be the requirement to meet the reduced emissions regulations in the future. The purpose of this study is to investigate the effects on the vehicle’s performance and exhaust emissions of the combustion process of blended crude jatropha oil and palm oil with different ratios. The engine speed was varied from 1500~3000 rpm, the load test condition was varied from 0~100% using a Dynapack chassis dynamometer and crude jatropha oil with a diesel blending ratio from 5~15vol% (CJO5~CJO15) was used. A decrease in HC emissions was found in the combustion process as the ratio of the blend of crude jatropha oil with diesel was increased and also with nearly equal engine performance. The increase in the jatropha oil biodiesel blending ratio promoted the reduction of HC, CO and CO2 emissions in the range 10vol% to 15vol% of the blends. The improvement in the combustion process with the higher blending ratio is expected to be strongly influenced by the oxygen contained in the blended crude jatropha oil.